The Employment Effects of Active Social Policy - Iben Bolvig; Peter Jensen; Michael Rosholm (Institute for the Study of Labor (IZA), 2003)
We analyse the effects of active social policy (ASP) on the dynamics of welfare dependence. We evaluate the impact of various ASP measures (employment and training) on the duration of welfare spells and subsequent employment spells, based on data from Denmark. The results show that employment measures improve the chances of leaving welfare dependence whereas training measures have detrimental effects on the exit rate from welfare spells. We investigate the optimal timing of ASP and show that there is a case for assigning individuals to early participation in employment programmes, as the net effect is larger the earlier participation begins.
Keywords: I38; J18; J68; J64; 330; employment effects; welfare dependence; active social policy; Workfare; Sozialpolitik; Arbeitsmarktpolitik; Wirtschaftspolitische Wirkungsanalyse; Beschäftigungseffekt; Schätzung; Dänemark